Parents of youth who self-injure: a review of the literature and implications for mental health professionals. Issue 1 (December 2015) - Arbuthnott, Alexis; Lewis, Stephen
Abstract Non-suicidal self-injury (NSSI) is a common mental health concern among youth, and parents can be valuable supports for these youth. However, youth NSSI can have a significant impact on parents' wellbeing, which may in turn alter parents' ability to support the youth. To date, no single article has consolidated the research on parents of youth who self-injure. This review synthesizes the literature on parent factors implicated in youth NSSI risk, the role of parents in help-seeking and intervention for youth NSSI, and the impact of youth NSSI on parent wellbeing and parenting. Clinical implications for supporting parents as they support the youth are also discussed, and recommendations for future research are outlined.